2013
DOI: 10.1002/mus.23927
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of denervated muscle to contractures after neonatal brachial plexus injury: Not just muscle fibrosis

Abstract: Contractures after NBPI cannot be explained solely by muscle fibrosis, arguing for investigation of alternate pathophysiologic targets for contracture prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 40 publications
(45 reference statements)
4
40
1
1
Order By: Relevance
“…Some studies reported muscular fibrosis after central or peripheral nervous system disorders [2,35] and are consistent with our results. In our animal study, muscular fibrosis after spinal cord injury was not improved by any treatments, but stretching after heat improved the muscular factor of contractures.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some studies reported muscular fibrosis after central or peripheral nervous system disorders [2,35] and are consistent with our results. In our animal study, muscular fibrosis after spinal cord injury was not improved by any treatments, but stretching after heat improved the muscular factor of contractures.…”
Section: Discussionsupporting
confidence: 93%
“…We evaluated muscular fibrosis, which contributes to poor muscle extensibility in muscular contracture [2,35], by a slight modification of the method according to Hadi et al [13]. Four samples of biceps femoris were randomly selected from each group.…”
Section: Quantification Of Fibrosis In Muscle Tissuementioning
confidence: 99%
“…Nikolaou has shown that functional shortening of denervated muscle plays a primary role in contracture pathogenesis [32]. However, the mechanism of contracture development in denervated muscle remains unanswered [33,34].…”
Section: Natural Historymentioning
confidence: 99%
“…In fact, shoulder contracture appeared only after the first week of the neural injury. Subscapularis thickness and weight decrease were also substantially higher than those in the imbalance model with a severe subscapularis muscle fiber atrophy . In our model of complete neurotmesis of both superior and inferior subscapularis nerves, reinnervation was impossible.…”
Section: Discussionmentioning
confidence: 51%
“…Subscapularis thickness loss is a consistent MRI finding in patients with an internal rotation contracture and glenohumeral joint dysplasia . The pathogenesis of subscapularis changes seems to be multifactorial and derived from an alteration in muscle growth both in length and thickness, by either shoulder rotation imbalance, subscapularis denervation, or both …”
Section: Discussionmentioning
confidence: 93%